Band of Brothers or Dysfunctional Family? A Military Perspective on Coalition Challenges During Stability Operations - Glenn, Russell W. (RAND Corporation, 2011)
During stability operations, coalitions must incorporate participation by government agencies other than the military, the indigenous government, and its population more than is expected during conventional combat operations. This book investigates challenges confronting coalitions today and considers potential solutions that include questioning the conception of what constitutes a coalition in today's world.